A Locally Manufactured Laser Gate was Employed to Assess the Agility of College Volleyball Players. - Muhammad Syaleh; Agung Nugroho; Muhammad Eka Mardyansyah Simbolon; Dzihan Khilmi Ayu Firdausi; Fredy Eko Setiawan (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Introduction: Agility is essential in volleyball. Accurate measurement helps identify talent, improve training, and reduce injury risk. However, common methods such as the T-agility test have limits in accuracy and practicality. Therefore, sensor-based technologies are developed to provide more objective and precise results. Objective: This study aims to create a low-cost and practical sensor system to measure volleyball agility. It focuses on developing a laser-based timing gate and evaluating its validity and reliability within a single session. Methodology: The participants were 25 collegiate volleyball players (age: 19.0 ± 0.88 years; height: 161.9 ± 7.19 cm; weight: 53.6 ± 9.15 kg). Each participant performed the T-test twice, and the average score was used for analysis. Intra-session reliability was assessed using the Intraclass Correlation Coefficient (ICC). Results: The laser timing system showed slightly faster results than the stopwatch in the first trial, slower results in the second, and overall faster average times across trials. Discussion: A low-cost laser-based agility system was successfully developed and tested against a manual stopwatch. The findings indicate acceptable validity and reliability. Faster times from the laser system are likely due to the removal of human reaction delays. This system is affordable, simple to use, and suitable as an alternative to expensive commercial timing devices, allowing wider access to objective performance measurement. Conclusions: The laser timing gate is a reliable and economical tool for assessing agility in volleyball players and is useful for research and training purposes.